(untitled) (Research, Society and Development, 2020)
This study assessed the laws governing education in the Brazilian State from the Federal Constitution of 1988 (art. 6º, art. 205, art. 206, art. 208) with the aim of addressing education as a social right, as well as understanding it as a fundamental right that depends on citizenship for its realization. The research following a qualitative approach, with collection of bibliographic-documentary data in order to help us understand and interpretation of constitutional articles. We realize that constitutional legislation systematizes mechanisms that provide support for laws and projects aims at to improve education and citizenship. In addition, for the materialization of constitutional articles the citizens must know their rights and duties to achieve on collective action. Therefore, it is necessary that each citizen understands the legislation in order to demand the real fulfillment of a society like the Brazilian.